Analisis Kontribusi PBB dan PDAM Terhadap Peningkatan Pendapatan Asli Daerah di Kota Surakarta, Karanganyar, dan Sukoharjo Tahun 2019-2024: Survei pada Kantor Pajak di Kota Surakarta, Karanganyar dan Sukoharjo - Ramadan, Taufik; Kristianto, Djoko (Economic Reviews Journal, 2025)
This study aims to analyze the contribution of Land and Building Tax (PBB) and income from the Regional Water Company (PDAM) to the increase of Local Own-Source Revenue (PAD) in Surakarta City, Karanganyar Regency, and Sukoharjo Regency during the 2019–2024 period. The method used is a quantitative approach through a case study using secondary data from PAD, PBB, and PDAM realization reports. Descriptive and statistical analyses show that both PBB and PDAM significantly contribute to PAD, with Surakarta demonstrating the highest contribution among the three regions. The partial test (t-test) reveals that both PBB and PDAM have a significant effect on PAD. The simultaneous test (F-test) also indicates that these variables collectively influence PAD significantly. These findings highlight the importance of optimizing the management of PBB and PDAM to enhance regional fiscal independence.